Searching for Balance: Water Rights, Human Rights and Water Ethics - Moench, Marcus (Water Nepal, 2003)
Worldwide, the many debates over water management emphasise the importance of establishing secure rights systems as the foundation for the efficient and equitable allocation of scarce freshwater resources. This perspective follows from global statements recognising water as an economic good and from pragmatic considerations regarding the incentives individuals have to waste resources in the absence of clear ownership rules. Private, tradable rights are the foundation for water allocation systems based on market mechanisms. According to economic theory, private rights and the presence of a market should also provide strong incentives for individuals to use water as efficiently as possible. The above pragmatic perspective has formed the basis for many efforts in many countries to reform water rights systems. There is, however, increasing dissonance between this perspective and a broad array of values or perspectives held by local water users and others who may lack formal legal rights but whose interests are affected either directly or indirectly by water allocation decisions. When rights to any resource are allocated or claimed by any one group of individuals, other individuals will lose their right to that resource and also to the values it supports. This raises questions concerning the legitimacy of the initial allocation system and whether or not those losing rights did so willingly and in an informed manner. It also raises questions regarding the authority of those who allocate rights to make such an allocation. This issue is particularly fundamental when, as in the case of water, the resource being allocated is essential for life. Access to water is essential for human survival and the right to life is recognised as fundamental in many religions, national constitutions and international agreements. Should, then, access to a basic minimum of water be classified as a human right? Taking it a step further, is a human right being violated when water is privatised or private rights to water are issued? Classifying access to water as a human right would pull the chords of emotive and legally powerful global institutions. This said, however, arguments about the denial of human rights are most often associated with acts of commission – such as murder, torture and genocide – as opposed to acts of omission – such as the failure of a government to provide for the basic needs of its people. In general, questions about access to water for fundamental needs are more acts of omission or at most diffused commission (such as the depletion of groundwater aquifers by thousands of individual users) rather than the direct violations associated with what are commonly perceived as human rights abuses. Furthermore, looking at water through a human rights lens may obscure many of the basic ethical issues inherent in the growing effort to develop private rights systems. My perspective, articulated in this paper, is that it may be more appropriate to recognise a new category of basic rights or entitlements which differs from – but which complements – those rights commonly falling in the human rights category. This new category would not carry the sets of associations already embedded in debates over human rights. Instead it would capture and give voice to many of the fundamental ethical issues inherent in different approaches to the allocation and management systems water and other natural resources. Drawing on examples from the western US, South Asia and the Islamic world, this paper explores themes in the growing debate over water rights systems. The economic logic underlying current efforts to reform rights systems is discussed first. A discussion of the social and historical roots of concepts emphasising the public ownership of water and providing for the role of the state owner or trustee of water resources follows. Private rights approaches, the counterpart of public ownership, are discussed next, followed by an exploration of ethical issues inherent in different rights systems. Particular attention is given to the ethical foundations of other rights systems such as those evolving for intellectual property. The subsequent section focuses on links to debates over human rights and the utility of using a human rights lens for looking at water issues. The final section explores potential alternatives and introduces notions of a ‘basic ethics’ framework. Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.165-183